-6-2y=0

Simple and best practice solution for -6-2y=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6-2y=0 equation:


Simplifying
-6 + -2y = 0

Solving
-6 + -2y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + -2y = 0 + 6

Combine like terms: -6 + 6 = 0
0 + -2y = 0 + 6
-2y = 0 + 6

Combine like terms: 0 + 6 = 6
-2y = 6

Divide each side by '-2'.
y = -3

Simplifying
y = -3

See similar equations:

| 3+4u=-25 | | 3X-15=7x+80 | | 46=3w+10 | | 9/n=4/8 | | -5x+5y=8 | | ln(4x-2)=24 | | x^3=(1/27) | | lnx=13 | | x/3.1=0.4 | | 0=3y^2+10 | | 8x+24=8(x+3) | | x/8=5/16 | | F(n)=-8n+21 | | 3x=-2y+9 | | 14y/9y^2 | | 8x-(3+5x)=3(2x-7) | | 5a+3b=128 | | 5x-3x+4(x-6)=2 | | 11e-4=8+4e+7e | | 2y=13x | | 8x-6+2x=14+5x | | x=2/x-1 | | 0=3x^2+18+27 | | ((6x^(2)-24x)/(2x))/((x^(2)-16)/(7x^2)) | | -4x-9y=27 | | 5/5x-10 | | (x-y)-(-x+y)= | | X/12=36 | | 17d^2-6d=0 | | 4y+14+2y=8y+4 | | (3a-b)-(6a+2b)= | | 4(2x-5)=7(x+2) |

Equations solver categories